1994
DOI: 10.1063/1.466799
|View full text |Cite
|
Sign up to set email alerts
|

Primary and secondary dissociation pathways in the ultraviolet photolysis of Cl2O

Abstract: The photodissociation of dichlorine monoxide (Cl,O) at 308, 248, and 193 nm was studied by photofragment translational energy spectroscopy. The primary channel upon excitation at 308 and 248 nm was Cl-O bond fission with production of ClO+Cl. A fraction of the Cl0 photoproducts also underwent spontaneous secondary dissociation at 248 nm. The center-of-mass translational energy distribution for the ClO+C!l channel at 248 nm appeared to be bimodal with a high energy component that was similar in shape to the 308… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 30 publications
3
31
1
Order By: Relevance
“…Plane and Husain [1060] reported that ~0.01 of the Na product is in the 3 2 P excited state, while Griffin et al [527] report a Na 3 2 P product branching ratio of 0.14±0.04. This difference is consistent with the orbital correlation predictions of products for reaction of each NaO state as presented by Herschbach et al [578]. (Table: 06-2, Note: 06-2) Back to Table J5.…”
Section: -104supporting
confidence: 80%
See 1 more Smart Citation
“…Plane and Husain [1060] reported that ~0.01 of the Na product is in the 3 2 P excited state, while Griffin et al [527] report a Na 3 2 P product branching ratio of 0.14±0.04. This difference is consistent with the orbital correlation predictions of products for reaction of each NaO state as presented by Herschbach et al [578]. (Table: 06-2, Note: 06-2) Back to Table J5.…”
Section: -104supporting
confidence: 80%
“…The main photolysis products are Cl and ClO. Using a molecular beam technique, Nelson et al [578] found Cl + ClO to be the only primary photodissociation channel at 308 nm, a major channel at 248 nm, and a minor channel at 193 nm. At 248 nm a fraction of the photoproduct ClO underwent spontaneous photodissociation.…”
Section: -95mentioning
confidence: 99%
“…As we reported in a previous publication, 1 the formation of ClϩClO products ͑ ⌬H 0 o ϭ33.8 kcal/mol͒ 2 is the only channel observed for Cl 2 O photolysis at 308 nm and is the major channel at 248 nm. We have repeated the Cl 2 O photolysis experiment at 248 and 308 nm and present here a refinement of the analysis for the ClϩClO channel.…”
Section: Introductionmentioning
confidence: 52%
“…Nelson et al [14] have studied the photolysis of the analogous chlorine compound, Cl 2 O, at 193, 248, and 308 nm. They used the technique of photofragment translational energy spectroscopy to identify the various photolysis channels.…”
Section: Br 2 O Photolysismentioning
confidence: 99%